Use of topical nasal steroid spray in the treatment of non-speciﬁc chronic pharyngitis- our experience - Gul, Naveed; Manhas, Monica; Kalsotra, Parmod; Deva, Faizah; Mir, Mehak Taban (International Journal of Research in Medical Sciences, 2021)
Background: The present study was done to find the effectiveness of nasal steroid spray in the treatment of non-speciﬁc chronic pharyngitis. Methods: The present prospective study was carried out in department of Otorhinolaryngology and Head and Neck surgery, Government Medical College Jammu from July 2017 to March 2020. Patients were selected randomly from the ENT OPD, a detailed history was taken, thorough clinical examination was done to conﬁrm the diagnosis and exclude all other existing illnesses and associated problems. Fluticasone nasal spray was used to see the relief of symptoms. Persistent relief was central to be considered proof of effectiveness of the treatment. Results: 40 patients were taken up for the present study, out of which only 32 patients showed relief in symptoms. 25 patients showed relief of symptoms with only 1-2 sprays. 8 patients did not report any relief of symptoms even after continues use of steroid nasal spray for 3-4 weeks. No significant side effect was noticed in any patient. Conclusions: In the present study, it is concluded that use of steroid (fluticasone) nasal spray in well selected cases of non-specific chronic pharyngitis is very effective, safe and cheap.